HOW ENGLISH LEARNER SUCCEEDED IN DIFFICULT CIRCUMSTANCES - Alpino Susanto (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2016)
This paper gives attention to Indonesian Ph.D students that have some challenges in learning English. The circumstance contexts of Batam as boarder zone to neighbor countries such as Singapore and Malaysia are exposed.  As the interview data focus on the Ph. D students in Malaysia, being lecturer in Batam, few sample could be explored but deeply in a focus group discussion. Researcher asks why a few individuals succeed in achieving competence in English where the majority is more fail understandably. The research theory of individual learner differences such as aptitude, motivation and learning strategy, have been included even though in the foreign language learner context, less empirical investigation of whether the factors could explain Foreign Language achievement.  This could be due to the exposure to use of English is  severely limited. It is known that classroom behavior must be understood in its social and cultural context. A small-scale exploratory study into the attitudes, learning behavior and English achievement of the 7 Ph.D students in Batam has been reported. Analysis of interview data shows that formal and informal learning opportunities seem a bit scarce, frustrating most English learners. Through the students as the respondent has demonstrated a personal investment to learn, and resourcefulness to pursue their goals independently.Keywords: Language Learner, Circumstances